BREVE ANÁLISE DOS IMPACTOS AMBIENTAIS URBANOS EM MOSSORÓ/RN - da Conceição Freitas Moura, Maria; Carvalho Serafim de Oliveira, Ludimilla (Electronic Journal "Fórum Ambiental da Alta Paulista", 2010)
.